(3QSGdI aj GdefWbs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje EYde Cf ai JUhQ GdhLhO KdGKI CbhGd Gdbhd GdChd Efg HOjgi hgh GdeNJGQ bGd ai TQM GdebUGO hGdMb Cf JUhQ GdhLhO GdHOjgi s
(3BNQgG (B:s
(3hPcQ ai TQM GdebUGO Cf chf GdYde SjeG GdYde HeG dG JMbb dg ai GdCYjGf ebJVjkG dKHhJ CeQ ai GdPgf XGgQ jLQi eLQi GdVQhQjGJ JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdadSaI hGdefWbs